2005
DOI: 10.1021/ja050389w
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Mesoporous Silica-Immobilized 1,3-Diphenylpropane. Impact of Pore Confinement and Size

Abstract: Mesoporous silicas such as SBA-15 and MCM-41 are being actively investigated for potential applications in catalysis, separations, and synthesis of nanostructured materials. A new method for functionalizing these mesoporous silicas with aromatic phenols is described. The resulting novel hybrid materials possess silyl aryl ether linkages to the silica surface that are thermally stable to ca. 550 degrees C, but can be easily cleaved at room temperature with aqueous base for quantitative recovery of the organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 63 publications
7
73
1
Order By: Relevance
“…1 for the adsorption isotherms) in all cases. It is critical to maintain the same pore diameters among all catalysts because previous studies demonstrated that the pore diameter affects the cooperativity between amines and surface silanols [3,[59][60][61][62][63]. The amine functionalization procedure did not alter the pore diameter, indicating that the procedure was sufficiently mild.…”
Section: Physical Characterization Of Materialsmentioning
confidence: 99%
“…1 for the adsorption isotherms) in all cases. It is critical to maintain the same pore diameters among all catalysts because previous studies demonstrated that the pore diameter affects the cooperativity between amines and surface silanols [3,[59][60][61][62][63]. The amine functionalization procedure did not alter the pore diameter, indicating that the procedure was sufficiently mild.…”
Section: Physical Characterization Of Materialsmentioning
confidence: 99%
“…On the other hand, for all SBA-15-supported ruthenium species, Ru/Si-9, Ru/Si-8, and Ru/Si-7, the racemization efficiency decreased with increasing pore size, 15 whereas the Ru-catalyzed acylation was totally suppressed (entries 2−4). Catalysts supported on SBA-15 exhibited selectivity over racemization and acylation.…”
Section: Microreactor Function Of the Mesoporous Silicasupported Ruthmentioning
confidence: 99%
“…[182][183][184] Grafting is commonly carried out by silylation on free ( Si-OH) and geminal silanol (¼ Si(OH) 2 ) groups. If a high surface coverage with functional groups is desired, it is important to maintain a large amount of surface silanol groups after removal of the surfactant.…”
Section: Surface Functionalizationmentioning
confidence: 99%